Acute Brucellosis Presenting as an Autoimmune Hemolytic Anemia - Durga Shankar Meena; Vikram Singh Sonwal; Amit Kumar Rohila; Vasudha Meena (Case Reports in Infectious Diseases)
Brucellosis is one of the most widespread zoonosis in the world. Hematological complications in brucellosis usually present as mild anemia, leukopenia, or pancytopenia. Autoimmune hemolytic anemia in brucellosis is rarely reported. Here, we report an 18-year-old female presented to us with progressive fatigue, jaundice, and fever. Hematological investigations revealed hemolytic anemia. Direct Coombs test was positive. Further evaluation showed positive serology and culture for Brucella. The patient was diagnosed with brucellosis with autoimmune hemolytic anemia. She was put on rifampicin and doxycycline along with corticosteroids. After 6 weeks, the patient was symptomatically improved with complete remission of hemolytic anemia. The possibility of brucellosis should be considered as a differential diagnosis of autoimmune hemolytic anemia, especially those living in the endemic areas.